Perubahan Nilai CBR Pada Tanah Lempung Yang Dicampur Abu Tandan Sawit - Ningrum, Puspa; Toyeb, Muhammad; Husnah, Husnah (Program Studi Teknik Sipil Sekolah Tinggi Teknologi Pekanbaru, 2022)
CBR (California Bearing Ratio) value is usually used to determine the bearing capacity of a soil type. Soil conditions with low bearing capacity are often found in clay soil types. There are several ways to increase the CBR value of clay, one of which is by adding palm bunch ash. In this research, an analysis of changes in the CBR value of clay with addition of 5%, 7.5%, and 10% palm oil bunch ash. The results showed that the largest CBR value was obtained at the addition of 10% of palm oil bunch ash, which was 7.493%.